2022
DOI: 10.1002/adma.202108020
|View full text |Cite
|
Sign up to set email alerts
|

Oriented 2D Perovskite Wafers for Anisotropic X‐ray Detection through a Fast Tableting Strategy

Abstract: 2D perovskite single crystals have emerged as excellent optoelectronic materials owing to their unique anisotropic properties. However, growing large 2D perovskite single crystals remains challenging and time‐consuming. Here, a new composition of lead‐free 2D perovskite—4‐fluorophenethylammonium bismuth iodide [(F‐PEA)3BiI6] is reported. An oriented bulk 2D wafer with a large area of 1.33 cm2 is obtained by tableting disordered 2D perovskite powders, resulting in anisotropic resistivities of 5 × 1010 and 2 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 43 publications
0
69
0
Order By: Relevance
“…Quasi-two-dimensional (quasi-2D) perovskites are solution-processable and combine the advantages of excellent charges carriers’ dynamics behavior of 3D perovskite and good stability of 2D perovskite 22 26 . Their unique optoelectronic properties of anisotropic quantum confinement, tunable bandgap, and defect tolerance nature enable attracting applications in photovoltaic 27 , 28 , light-emitting diode (LED) 29 , 30 , laser 31 , X-ray detectors 32 35 , and photodetectors 4 . Spray-coated perovskite films for solar cells have been reported for large area devices 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Quasi-two-dimensional (quasi-2D) perovskites are solution-processable and combine the advantages of excellent charges carriers’ dynamics behavior of 3D perovskite and good stability of 2D perovskite 22 26 . Their unique optoelectronic properties of anisotropic quantum confinement, tunable bandgap, and defect tolerance nature enable attracting applications in photovoltaic 27 , 28 , light-emitting diode (LED) 29 , 30 , laser 31 , X-ray detectors 32 35 , and photodetectors 4 . Spray-coated perovskite films for solar cells have been reported for large area devices 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the application of halide perovskite thin films in solar cells with amazingly fast increasing power conversion efficiencies has attracted much attention in the field of optoelectronics . Moreover, other halide perovskite-based applications such as LEDs as well as photo- and X-ray detectors were also demonstrated. In the case of perovskite X-ray detectors, especially single-crystal-based devices showed remarkably high sensitivities. , However, as the integration of perovskite single crystals in industry-relevant length scales and geometries remains challenging, perovskite powder-based thick films represent an attractive alternative for a versatile realization of perovskite X-ray detectors. …”
Section: Introductionmentioning
confidence: 99%
“…112 Moreover, Li et al demonstrated the anisotropic X-ray detection in 2D perovskite 4-fluorophenethylammonium bismuth iodide [(F-PEA) 3 BiI 6 ] wafers. 113 The resistivity of this wafer was found as 5 × 10 10 Ω cm in the lateral direction and 2 × 10 11 Ω cm in the vertical direction, which shows the anisotropic carrier transport in this material. In the lateral direction, the μτ product was estimated as 4 × 10 −4 cm 2 V −1 , which is significantly higher than the vertical direction ( 8 10 −5 cm 2 V −1 ) because the continuous bismuth halide octahedral sheets provide a smooth charge carrier transport in the vertical direction.…”
Section: Anisotropic Performance Of Pscs Based Devicesmentioning
confidence: 81%
“…Moreover, Li et al. demonstrated the anisotropic X-ray detection in 2D perovskite 4-fluorophenethylammonium bismuth iodide [(F-PEA) 3 BiI 6 ] wafers . The resistivity of this wafer was found as 5 × 10 10 Ω cm in the lateral direction and 2 × 10 11 Ω cm in the vertical direction, which shows the anisotropic carrier transport in this material.…”
Section: Anisotropic Performance Of Pscs Based Devicesmentioning
confidence: 99%